A Global Survey on the Perception of Conservationists Regarding Animal Consciousness - Valentine Yakhlef; Manuel Magalhães-Sant’Ana; Ana Luísa Pereira; Alexandre Azevedo (Animals, 2025)
Human perceptions of animal consciousness have evolved over time, influencing how they are treated. This study aimed to assess perceptions of animal consciousness in people working in conservation. An online survey of 87 participants evaluated their perceptions of animals’ capabilities across 10 dimensions of consciousness, including self-consciousness, learning, and reasoning. The sum of the answers to the questions was validated as a “perception index” using a principal component analysis. Next, its variation according to taxonomic, demographic, professional factors, and the duration, type, and frequency of interaction with animals was assessed with generalized linear models and stepwise model selection. Participants’ perceptions varied with taxonomic class and the level of education, with mammals obtaining higher indexes than birds (−0.14; 95% confidence interval [CI] −0.24, −0.03, p < 0.01) or reptiles (−0.41; 95% CI −0.55, −0.27, p < 0.01), and respondents holding a PhD exhibiting higher perception indexes than those with BScs (−0.19; 95% CI −0.32, −0.06, p < 0.01) or lower education (−0.18; 95% CI −0.32, −0.03, p = 0.01). The attribution of consciousness followed a phylogenetic pattern, but several exceptions (e.g., the octopus and raven) were noted on a finer scale supporting a multifactorial influence on the perception of animal consciousness that emerges upon a baseline phylogenetic pattern. Finally, the results suggest that conservationists are influenced by culture and scientific knowledge, as much as their personal experiences, when evaluating animals’ perceptions, highlighting the need for further research on the convergence between perception, belief, and evidence.